2007
DOI: 10.1017/s0007485307005238
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation and improvement of sticky traps as monitoring tools for Glossina austeni and G. brevipalpis (Diptera: Glossinidae) in north-eastern KwaZulu-Natal, South Africa

Abstract: The attractiveness of various colours, colour combinations and sizes of sticky traps of the 3-dimensional trap (3DT), cross-shaped target (XT), rectangular screen (RT) and monopanels were evaluated for their efficacy to capture Glossina austeni Newstead and G. brevipalpis Newstead in north-eastern KwaZulu-Natal, South Africa. The 3-dimensional shapes of the XT and 3DT in light blue (l.blue) and white were significantly (ca. 3.1-6.9 times) better than the RT for G. austeni. On bicoloured XTs, G. austeni landed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 17 publications
0
7
0
Order By: Relevance
“…Between 1993 and 1999, extensive tsetse fly surveys were conducted in an area of approximately 12 000 km 2 using odour-bated sticky XT traps (cross-shaped targets) to assess the distribution of each species ( Figure 1a, b ) (Kappmeier & Nevill 1999a , Kappmeier Green & Venter 2007 ). The survey indicated that G. brevipalpis was present in southern and northern bands, commonly associated with game reserves and other protected areas.…”
Section: Introductionmentioning
confidence: 99%
“…Between 1993 and 1999, extensive tsetse fly surveys were conducted in an area of approximately 12 000 km 2 using odour-bated sticky XT traps (cross-shaped targets) to assess the distribution of each species ( Figure 1a, b ) (Kappmeier & Nevill 1999a , Kappmeier Green & Venter 2007 ). The survey indicated that G. brevipalpis was present in southern and northern bands, commonly associated with game reserves and other protected areas.…”
Section: Introductionmentioning
confidence: 99%
“…In South Africa the envisaged tsetse infested area (16 000 km 2 ) stretches from around 10 km south of the Mfolozi River in the south, for approximately 190 km, to the border of Mozambique in the north, and from the Indian Ocean coast in the east for 80 km to the Hluhluwe-iMfolozi Park in the west ( Fig 1 ) [ 7 , 8 ]. The infested area extends into the Matutuine District (8 500 km 2 ) (MP) of Mozambique, the northern limit being the Boane and Namaacha Districts of Mozambique [ 6 , 11 ].…”
Section: Methodsmentioning
confidence: 99%
“…This southern population extends into the neighbouring Maputo Province (MP) of Mozambique [ 6 – 11 ]. Of the 31 described tsetse fly species and subspecies, only two species are found as far south as South Africa, i.e., Glossina brevipalpis Newstead belonging to the Fusca (forest) species group and Glossina austeni Newstead belonging to the Morsitans (savannah) species group [ 1 , 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations